Odpowiedzi

Najlepsza Odpowiedź!
2009-12-13T17:01:32+01:00
1) m1 a = m1 g - N
m2 a = N

m1 a = m1 g - m2 a
m1 a + m2 a = m1 g
a ( m1 + m2 ) = m1 g
a = (m1 / ( m1 + m2 )) g

2) m1 a = m1 g - N
m2 a = N => a = N / m2

m1 * N / m2 = m1 g - N obie strony mnożymy przez m2
m1 N = m1 m2 g - N m2
m1 N + m2 N = m1 m2 g
N ( m1 + m2 ) = m1 m2 g
N = (( m1 m2 ) / (m1 + m2)) g
2009-12-13T17:11:06+01:00
M₁ a = m₁ g - N
m₂ a = N
dodajemy stronami
m₁a + m₂a = m₁g - N + N
m₁a + m₂a = m₁g
a(m₁ + m₂) = m₁g
a = m₁g/m₁ + m₂ = (m₁/m₁ + m₂)g
N = m₂a - za a wstawiamy (m₁/m₁ + m₂)g
N = m₂(m₁/m₁ + m₂)g = (m₁m₂/m₁ + m₂)g